Eksploitasi Mikroorganisme Laut Dalam: Tantangan Baru Dalam Rezim Hukum Laut Internasional - M. Gerry Alfandos; M. Farhan Hasan; Adib Kumara Reisman (GLOBAL SCIENTS PUBLISHER, 2026)
The advancement of marine biotechnology in the 21st century has transformed deep-sea microorganisms into highly valuable objects of exploitation, particularly due to their potential in the pharmaceutical industry, industrial enzymes, and biofuels. However, behind this promising prospect, the existing international law of the sea regime—primarily UNCLOS 1982—has not been able to adequately regulate the utilization of marine genetic resources (MGR), especially in areas beyond national jurisdiction (ABNJ). This study aims to analyze two main issues: first, the normative gaps and ambiguities within UNCLOS regarding deep-sea MGR; and second, the extent to which the 2023 BBNJ Agreement is capable of addressing these legal challenges. The method employed is normative legal research through a juridical-normative approach, drawing on international regulations, legal doctrines, and relevant scientific literature. The analysis reveals that the regulatory vacuum in UNCLOS has created significant disparities in access between developed and developing countries, opened opportunities for biopiracy, and threatened the sustainability of highly vulnerable deep-sea ecosystems. The 2023 BBNJ Agreement represents an important step forward, yet several issues remain unresolved, including the regulation of Digital Sequence Information (DSI) and concrete implementation mechanisms. This study also formulates policy recommendations for Indonesia as an archipelagic state with substantial strategic interests in the international governance of deep-sea MGR.